The History Problem The Politics of War Commemoration in East Asia - Saito, Hiro (University of Hawai'i Press, 2016)
Seventy years have passed since the end of the Asia-Pacific War, yet Japan remains embroiled in controversy with its neighbors over the war's commemoration. Among the many points of contention between Japan, China, and South Korea are interpretations of the Tokyo War Crimes Trial, apologies and compensation for foreign victims of Japanese aggression, prime ministerial visits to the Yasukuni Shrine, and the war's portrayal in textbooks. Collectively, these controversies have come to be called the "history problem." But why has the problem become so intractable? Can it ever be resolved, and if so, how? To answer these questions, Hiro Saito mobilizes the sociology of collective memory and social movements, political theories of apology and reconciliation, psychological research on intergroup conflict, and philosophical reflections on memory and history.